1990
DOI: 10.1111/j.1365-2958.1990.tb00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Listeria monocytogenes‐specific protein capable of inducing delayed hypersensitivity in Listeria‐immune mice

Abstract: Recovery of the host after infection by the intracellular pathogen Listeria monocytogenes is dependent on cell-mediated immunity. Little is known of the nature of listerial antigens that induce cell-mediated responses in the infected host. In this study we report on the identification and cloning of an Escherichia coli recombinant encoding a listerial antigen, designated ImaA, capable of eliciting a specific delayed-type hypersensitivity response in Listeria-immune mice. Nucleotide sequencing of the Listeria D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 30 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…The lmaA gene was previously shown to encode a listerial antigen capable of eliciting a delayed-type hypersensitivity reaction in Listeria-immune mice (13). These studies also indicated that the lmaA gene is a highly specific marker for pathogenic Listeria spp.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The lmaA gene was previously shown to encode a listerial antigen capable of eliciting a delayed-type hypersensitivity reaction in Listeria-immune mice (13). These studies also indicated that the lmaA gene is a highly specific marker for pathogenic Listeria spp.…”
mentioning
confidence: 84%
“…The resulting plasmid was named pLM68.1.1 and encodes the LmaD polypeptide. For expression of lmaA, we chose the recombinant plasmid pLM10, which was described previously (13). The inserts of all constructs used in this study were verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The probe for lmaAB was made in the same way with oligonucleotides GATTATACACCGGGAGCTGCTAAAG (positions 415 to 439 in Gohmann et al [11]) and GCCCTCAGTAATCGT TAAATCAACAAG (positions 829 to 855 in Gohmann et al [11]). The probe for hly was a 410-bp HindIlI fragment containing the distal end of the gene (22).…”
Section: Methodsmentioning
confidence: 99%
“…Gohmann et al described antigens that elicit an immune response during Listeria infection (36). One of the proteins was named antigen A (lmaA), and it is encoded by ftbG.…”
Section: Discussionmentioning
confidence: 99%